The effect of aqueous leaf extract of telfaria occidentalis on isolated guinea pig ileum (2001)
The effect of aqueous extract of Telfaria occidentalis was studied in vitro on the guinea pig ileum. The extract elicited a dose dependent contractions of the ileum. These responses were blocked by 5 x 10 M mepyramine and 5 x 10-M.atropine, suggesting that it has both histominergic and cholinergic properties. The usefulness of the plant as potent naturally available purgative is presented in this study.